Travels of terror : strange and spooky spots across America - Florence, Kelly; Hafdahl, Meg (Sourcebooks, 2024)
"Horror, true crime, and creepy legends abound in this epic travel guide to the films, books, and dark history found throughout the U.S. With a unique eye focused on the female, best friends and lifelong horror fans, Meg Hafdahl and Kelly Florence, will tour well-known sites like the Lizzie Borden Bed and Breakfast, while also going off-trail to explore forgotten gems, like the hometown of the OG goth girl, Emily Dickinson, capturing the truly strange and gothic in America. Every chapter will include their own, authentic experience, travel tips, strange facts, maps, and more. With experiential travel continuing to gain momentum and gothic/witchy lifestyles going mainstream, this book will give horror and true crime readers the ultimate guide to planning macabre trips of their own"--